Strategi Pembelajaran PAI dalam Pembentukan Karakter Siswa Melalui Media Sosial - Bahrudin; Udin Supriadi; Pandu Hyangsewu (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research discusses the role of social media in supporting Islamic Religious Education (PAI) learning and student character formation. In addition, this research highlights the various challenges and opportunities faced in the use of social media in educational environments, as well as the importance of policies that support the wise use of technology in developing the younger generation. The aim of this research is to evaluate the extent to which social media is effective as a PAI learning tool in shaping student character. Along with technological developments, social media offers various opportunities as an interactive and easily accessible learning platform, especially in delivering PAI material that focuses on character formation. This research uses qualitative methods with data collection techniques through interviews, observation and documentation. Primary data was collected through direct observation of PAI learning activities in schools, while secondary data was taken from relevant journals and scientific articles. Data analysis was carried out descriptively to provide an overview of students' perceptions and motivation in learning PAI with the support of technology used by teachers. The research results show that social media, such as WhatsApp, YouTube, and Instagram, are effectively used by PAI teachers to deliver material, hold discussions, and strengthen religious values ​​which play an important role in forming student character.